The Influence Of One Hole Game Media In Developing Fine Motor Skills In Early Childhood - Susanto Susanto (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
Introduction: Children's fine motor development is influenced by the use of educational games. There are types of educational games used in stimulating children's fine motor development, including one hole games. But unfortunately in the field, activities that can stimulate children's fine motor development are still not done adequately, in this case the frequency is still less than what is used. So that children's fine motor development becomes less than optimal. Aim: This study is to determine the effect of using educational game tools type one hole game on fine motor development of preschool children. Method: This study used a quasi experiment design with a pretest and posttest design. The sampling technique used purposive sampling of 25 respondents in the one hole game intervention group. Data collection methods using questionnaires and by observation. The assessment uses the DENVER II instrument sheet which is taken from the fine motor measurement aspect. Data analysis used was 2 dependent samples t test and 2 independent samples t test for bivariate. Result: The results prove that there is an effect of educational game intervention type one hole game on fine motor development of preschool children. Conclusion: Based on the results of the study, there is an effect of one hole game on fine motor development. To stimulate children's fine motor development, it is necessary to increase the frequency of games.